Prevalence and risk factors of hypertension among the bank employees of Western Maharashtra – a cross sectional study - Brahmankar, Tanuja R.; Prabhu, Priya M. (International Journal Of Community Medicine And Public Health, 2017)
Background: Hypertension, the “silent killer” - is a modern day’s epidemic and is becoming a public health emergency worldwide, especially in the developing countries. Sedentary life-style and stress are important risk factors for hypertension. The job of bank employees is both sedentary in nature and accompanies high levels of mental stress, thereby at a higher risk of developing hypertension. Hence the present study was conducted to study the prevalence and risk factors of hypertension among the bank employees in Western Maharashtra. Methods: A cross-sectional study was conducted during January 2014 to December 2015 to assess the prevalence and risk factors of hypertension among the bank employees in Western Maharashtra. By using multistage sampling method, total 340 bank employees from 40 branches were included in the study after fulfilling the inclusion and exclusion criteria. After all ethical considerations, the data were collected by using pre-designed, pre-tested and semi-structured questionnaire and then analysed using MS Excel, SPSS-22 and Primer of Biostatistics. Results: Overall prevalence of hypertension was 39.7% and that of pre-hypertension was 41.8% among the study population. Socio-demographic factors like age, male gender, family history of hypertension, mode of travel, physical activity, overweight, years of service, intake of coffee and smoking had shown significant association with hypertension. Conclusions: Prevalence of hypertension was found as significantly higher in bank employees than the general population of India. Among the non-hypertensives large part was pre-hypertensives which are also at high risk of developing hypertension in the future.